Durability of Slag Based Geopolymer Stabilized Clay with High Moisture Condition - Ahmad, Muhammad Munsif; Mohammad Zaki, Mohd Faiz; Md. Ghazaly, Zuhayr; Bawadi, Nor Faizah; Md Nujid, Masyitah; Muhamad, Khairunnisa; Ha Hou Hong, Terence (International Journal of Integrated Engineering, 2024)
Clay soils, characterized by their cohesiveness and water retention capacity, exhibit low aeration and tend to swell when water is absorbed, leading to subsequent contraction. The moisture content significantly affects the properties of marine clay, resulting in low strength and high compressibility. Traditional stabilizers like lime, cement, gypsum, fly ash, GGBS, and zeolite have been extensively studied for their ability to enhance the compressive strength, reduce swelling potential, and improve the overall durability of the soil. These stabilizers offer numerous benefits in terms of soil properties and have been extensively researched. A total of 27 GGBS-treated specimens and 7 cement-treated specimens were cast and tested for the strength and durability characteristic. In the study, the variables are binder content of 10%, 20%, and 30%, activator/binder ratio of 0.5, 0.75, and 1.0, and initial moisture content of 0.75wL, wL, and 1.25wL. Several kinds of experiments were carried out in order to investigate the qualities of stabilized clays, such as their unconfined compressive strength and their resistance to the effects of wetting and drying cycles. As the initial moisture content of the soil increased, the strength of the treated specimens decreased under unconfined compression and flexure. As a result, increasing the binder dose was necessary in order to achieve the strength requirements for high water content soils. Thus, it showed the use of a slag-geopolymer binder for the purpose of stabilizing soft soil is an alternative that is both effective and environmentally friendly.